2020
DOI: 10.3390/nu12123880
|View full text |Cite
|
Sign up to set email alerts
|

Ten SNPs May Affect Type 2 Diabetes Risk in Interaction with Prenatal Exposure to Chinese Famine

Abstract: Increasing studies have demonstrated that gene and famine may interact on type 2 diabetes risk. The data derived from the cross-sectional 2010–2012 China National Nutrition and Health Survey (CNNHS) was examined to explore whether gene and famine interacted to influence type 2 diabetes risk. In total, 2216 subjects were involved. The subjects born in 1960 and 1961 were selected as the famine-exposed group, whereas subjects born in 1963 were selected as the unexposed group. A Mass Array system was used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Fetal and childhood exposure to the Chinese famine, followed by high socioeconomic status during adulthood, were associated with increased T2DM incidence in several studies 80,81 . The effect of famine and malnutrition might be mediated by epigenetic changes 82,83 , decreased pancreatic β-cell proliferation and increased insulin resistance compared with individuals not exposed to famine or malnutrition 84 . In India, the prospective Pune Maternal Nutrition Study demonstrated that maternal undernutrition and vitamin B 12 prevalence observed in India and China, the known pancreatic β-cell defects associated with IFG and IGT and evidence from single-ethnic and multi-ethnic studies.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…Fetal and childhood exposure to the Chinese famine, followed by high socioeconomic status during adulthood, were associated with increased T2DM incidence in several studies 80,81 . The effect of famine and malnutrition might be mediated by epigenetic changes 82,83 , decreased pancreatic β-cell proliferation and increased insulin resistance compared with individuals not exposed to famine or malnutrition 84 . In India, the prospective Pune Maternal Nutrition Study demonstrated that maternal undernutrition and vitamin B 12 prevalence observed in India and China, the known pancreatic β-cell defects associated with IFG and IGT and evidence from single-ethnic and multi-ethnic studies.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…The full-text review identified 32 original studies relating the Chinese famine to T2D. Fourteen studies used identical or overlapping data sources from the Kailuan Group Health Examination [ 28 , 29 ], the China Kadoorie Biobank (CKB) [ 30 , 31 ], the China National Nutrition and Health Survey (CNNHS) 2010–2012 [ 32 , 33 ], the Survey on Prevalence in East China for Metabolic Diseases and Risk Factors Cohort (SPECT) [ 34 , 35 , 36 ], or the China Health and Retirement Longitudinal Studies (CHARLS) [ 37 , 38 , 39 , 40 , 41 ]. From these 14 studies, five studies were selected as the representative studies [ 28 , 30 , 33 , 34 , 38 ], and the other nine were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…When several studies were available on the same or overlapping cohorts reporting results of T2D and glucose dysregulation, we selected results from studies that either provided the most comprehensive information or had the largest sample size as representatives. Our search identified 14 Chinese famine studies on T2D using the same or overlapping data sources, including the Kailuan Group Health Examination, 25,26 China Kadoorie Biobank (CKB), 27,28 China National Nutrition and Health Survey (CNNHS) in 2010-12, 29,30 Survey on Prevalence in East China for Metabolic Diseases and Risk Factors Cohort (SPECT) in Shanghai, Jiangxi and Zhejiang, [31][32][33] China Health and Retirement Longitudinal Studies (CHARLS). [34][35][36][37][38] From them, five studies were selected as representative studies in our systematic review and meta-analysis.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%